Reduced Vision and Refractive Errors, Results from a School Vision Screening Program in Kanchanpur district of Far Western Nepal - Awasthi, S; Pant, B P; Dhakal, H P (Kathmandu University Medical Journal, 2012)
Background At present there is no data available on reduced vision and refractive errors in school children of far western Nepal. So, school screening records were used to obtain data useful for planning of refractive services. Methods Data are provided from school screening conducted by Geta Eye Hospital during February/March 2008. The cases with complete data sets on visual acuity, refractive error and age were included and analyzed using computer software. Results Of 1165 children (mean age 11.6±2.5 years) examined, 98.8% (n= 1151) had uncorrected visual acuity of 6/9 and better in at least one eye whereas 1.2% (n= 14) had acuity 6/12 and worse in both eyes. Among them, either eye of 9 children improved to 6/9 and better with correction. However, visual acuity was 6/12 and worse in both eyes of 5 children even after correction. There were 24 children with refractive errors (myopia, 1.54%; n= 18 and hypermetropia, 0.51%; n=6) in at least one eye. The spherical equivalent refraction was not significantly different with age and gender. Conclusions The incidence of reduced vision and refractive errors among school children of this semi rural district were low. http://dx.doi.org/10.3126/kumj.v8i4.6233 Kathmandu Univ Med J 2010;8(4):370-4